2023
DOI: 10.3390/pathogens12030406
|View full text |Cite
|
Sign up to set email alerts
|

Vector-Borne Pathogens in Guard Dogs in Ibadan, Nigeria

Abstract: Canine vector-borne diseases are of great relevance not only regarding animal welfare but also in relation to the One Health concept. Knowledge concerning the most relevant vector-borne pathogens in dogs is scarce and limited to stray dogs in most western African regions, and there is virtually no information about the situation in kept dogs presenting (regularly) to vets. Therefore, the blood samples of 150 owned guard dogs in the Ibadan area—in the southwest of Nigeria—were collected and analyzed for the DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…In 2017, Takeet et al [ 60 ] determined the prevalence of B. rossi in Abeokuta (capital city of Ogun State in southwest Nigeria), revealing that 39 of 209 dogs with unknown health status (18.7%) presented to various veterinary clinics and the Veterinary Teaching Hospital of the Federal University of Agriculture in Abeokuta were infected with the parasite [ 60 ]. However, another study from southwest Nigeria (Ibadan in Oyo State) found only 6 of 150 presumably both symptomatic and asymptomatic domestic guard dogs (4%) treated in a private veterinary clinic and the Veterinary Teaching Hospital in University of Ibadan were infected with B. rossi [ 61 ].…”
Section: Prevalence Of Babesia Rossimentioning
confidence: 99%
“…In 2017, Takeet et al [ 60 ] determined the prevalence of B. rossi in Abeokuta (capital city of Ogun State in southwest Nigeria), revealing that 39 of 209 dogs with unknown health status (18.7%) presented to various veterinary clinics and the Veterinary Teaching Hospital of the Federal University of Agriculture in Abeokuta were infected with the parasite [ 60 ]. However, another study from southwest Nigeria (Ibadan in Oyo State) found only 6 of 150 presumably both symptomatic and asymptomatic domestic guard dogs (4%) treated in a private veterinary clinic and the Veterinary Teaching Hospital in University of Ibadan were infected with B. rossi [ 61 ].…”
Section: Prevalence Of Babesia Rossimentioning
confidence: 99%
“…While A. platys is mainly a canine pathogen, it can occasionally be found in other animals such as cats, foxes, Bactrian camels, deer, sika deer, cattle, and humans [106]. In West Africa, the DNA of A. platys has been detected in dogs, camels, and cattle from Nigeria [55,113,[117][118][119], dogs from the Maio Island in the Cape Verde archipelago [120,121], dogs from Ghana and Côte d'Ivoire [71,73,118], and dogs, cattle, goats, and sheep from Senegal [68,105]. In ticks, the DNA of A. platys has been identified in Rh.…”
Section: Anaplasmosismentioning
confidence: 99%
“…Antibodies against E. canis have only been reported in West Africa from dogs in Côte d'Ivoire [136,137]. The DNA of E. canis has been found in dogs from Nigeria [38,55,[117][118][119][138][139][140][141], Senegal [68,142], Ghana [73], Cape Verde [120,121], and Côte d'Ivoire [143]. In ticks, the DNA of E. canis was detected in Rh.…”
Section: Ehrlichiosismentioning
confidence: 99%
See 1 more Smart Citation
“…This disease has a worldwide distribution in tropical, subtropical, and temperate countries in Europe [30], Asia [2], Africa [18], and North and South America [26], including Colombia [6].…”
Section: Introductionmentioning
confidence: 99%